The Influence Of Advertising, Price And Display On Purchasing Decisions At Indomaret Betungan Bengkulu City - Rikei Rafsanjani; Sulisti Afriani; Nurzam Nurzam (Journal of Indonesian Management, 2023)
Consumer purchasing decisions are an integration process that combines knowledge to evaluate two or more alternative behaviors, and choose one among them. This research aims to determine the influence of advertising, price and display on purchasing decisions at Indomaret Betungan Bengkulu, whether they influence simultaneously or whether they influence each other together. This type of research is quantitative descriptive, namely research that uses mathematical models, theories and/or hypotheses related to natural phenomena. The sample in this study used an accidental sampling technique, where the population was sampled at Indomaret Betungan when the researcher conducted the research. There is an influence of advertising (X1) on the purchasing decision (Y) of Indomaret Betungan Bengkulu with a sig value of 0.000 < 0.05 and t count > t table (6.760>0.135) thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X influences purchasing decisions (Y). There is an influence of price (X2) on the purchasing decision (Y) of Indomaret Betungan Bengkulu with a sig value of 0.005 < 0.05 and t count > t table (8.427>0.135) thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 influences purchasing decisions (Y). There is an influence of display (X3) on the purchasing decision (Y) of Indomaret Betungan Bengkulu with a sig value of 0.004 < 0.05 and t count > t table (6.909>0.135) thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X3 influences purchasing decisions (Y). Advertising, price and display together influence purchasing decisions with a value of Fsig < α where Fsig is 0.000 and the F count is 9.323, > F table 2.65.